Evaluation of the Budget Policy for the Empowerment of the Coastal Poor through the Development of an Integrated People's Salt Business with Geomembrane Technology 2018-2019 (Study in Aceh Utara Regency) - Saharuddin Saharuddin; Endang Larasati; Sri Suwitri; Ida Hayu Dwimawanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The approach used in this study uses a descriptive qualitative approach, which is a research that is included in the type of qualitative research. According to Moleong (2007), qualitative research is research that intends to understand phenomena about what is experienced by research subjects such as behavior, perceptions, motivations, actions, etc. holistically, and by means of descriptions in the form of words and language, in a context. Natural specialization and by utilizing various natural methods. The research focus has two objectives, firstly, by setting the research focus, it means limiting the extent of the study, thereby determining the research site more focused. Second, determining the focus will streamline the information received. Data collection techniques are the most important step in research, because the main purpose of research is to obtain data. The model of economic empowerment of salt farmers through PUGaR which leads to community-based participatory development (in this case cooperatives) is unable to respond to the local wisdom of salt farmers in North Aceh. Where the traditional salt management system done by family members. Those involved in salt production come from one family member consisting of father, mother, children and other cousins. if, through the PUGaR program, salt farmers must convert their business land into a community outside of their main family system. This pattern is then based on field findings contrary to the wishes of the community.